Effects of Butyrate Glyceride-based Ingredient Supplementation on Nursery Pig Performance, Fecal Dry Matter, Serum Chemistry, and Blood Characteristics - Ethan B. Stas; Ying Chen; Ross Wolfenden; Jason C. Woodworth; Mike D. Tokach; Joel M. DeRouchey; Robert D. Goodband; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2024)
A total of 2,238 pigs (Line 337 × 1050, PIC, Hendersonville, TN; initially 11.3 lb) were used to determine the effects of butyrate glyceride-containing feed additive supplementation on nursery pig growth performance, fecal consistency, blood criteria, and inflammatory markers. Butyrate is the main source of energy for epithelial cells and plays a key role in nutrient utilization. At weaning, pigs were allotted to one of six dietary treatments consisting of a control diet and four diets containing various butyrate glyceride-based feed additives (MTB C, C4 C Mix, MTB 40C, MTB 400C, Eastman Chemical, Kingsport, TN). The final diet contained a commercial feed additive (AviPlus S, Vetagro Inc., Chicago, IL) that is a combination of micro-encapsulated sorbic and citric acids and synthetic thymol and vanillin botanicals. Dietary treatments were fed over three phases. The control diet contained 3,000 and 2,000 ppm of Zn from ZnO in phase 1 and 2, respectively. The control diet also contained 55 ppm of carbadox (Mecadox; Phibro Animal Health Corp., Teaneck, NJ) in phase 1 and 2. Each feed additive was added at 0.3% to the control diet in phases 1 and 2, and 0.1% to the control diet in phase 3. Phase 1 and 2 diets were fed according to a feed budget of 5 and 12 lb/pig, respectively. Following phase 2 diets, pigs were fed phase 3 diets until the completion of the study. There were no significant differences between treatments for growth performance or serum haptoglobin for the duration of the study (P > 0.10). On d 10 of the study, pigs fed MTB 40C diets had increased (P < 0.05) fecal DM compared to pigs fed C4 C Mix and AviPlus S diets with other treatments intermediate. There was a treatment × day interaction (P = 0.041) for fibrinogen where pigs fed C4 C Mix diets had increased (P < 0.05) fibrinogen compared to pigs fed AviPlus S diets on d 10 of the study, but no differences between treatments on d 24 and 42. For IFNγ on d 10, pigs fed C4 C Mix had increased (P < 0.05) IFNγ concentration compared to MTB C and MTB 40C with other treatments intermediate. Minor treatment or day effects were also observed for other complete blood count measurements and cytokines. In conclusion, although no differences in growth performance were observed, pigs fed MTB 40C had improved d 10 fecal dry matter and exhibited lower concentrations of the pro-inflammatory cytokine IFNγ compared to C4 C Mix.
Keywords: butyrate glycerides; nursery pig; inflammatory cytokines